-1(x+3)-3=-6(x+8)

Simple and best practice solution for -1(x+3)-3=-6(x+8) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -1(x+3)-3=-6(x+8) equation:


Simplifying
-1(x + 3) + -3 = -6(x + 8)

Reorder the terms:
-1(3 + x) + -3 = -6(x + 8)
(3 * -1 + x * -1) + -3 = -6(x + 8)
(-3 + -1x) + -3 = -6(x + 8)

Reorder the terms:
-3 + -3 + -1x = -6(x + 8)

Combine like terms: -3 + -3 = -6
-6 + -1x = -6(x + 8)

Reorder the terms:
-6 + -1x = -6(8 + x)
-6 + -1x = (8 * -6 + x * -6)
-6 + -1x = (-48 + -6x)

Solving
-6 + -1x = -48 + -6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '6x' to each side of the equation.
-6 + -1x + 6x = -48 + -6x + 6x

Combine like terms: -1x + 6x = 5x
-6 + 5x = -48 + -6x + 6x

Combine like terms: -6x + 6x = 0
-6 + 5x = -48 + 0
-6 + 5x = -48

Add '6' to each side of the equation.
-6 + 6 + 5x = -48 + 6

Combine like terms: -6 + 6 = 0
0 + 5x = -48 + 6
5x = -48 + 6

Combine like terms: -48 + 6 = -42
5x = -42

Divide each side by '5'.
x = -8.4

Simplifying
x = -8.4

See similar equations:

| 5(x/5)-3(5)=5(x/5) | | 10=-7-3x | | -6z-9(-8z-4)=2-5(-9-z) | | 5(1-2x)+8=15 | | 6(x-3)-2(x-2)=1 | | 23=33-2(4-2w) | | 12/11•5/8 | | 12/8•5/8 | | 7(3x-2)=-39 | | -9x+3=-8x | | 9x+8=-1x-13 | | 3+.20y=2x+4 | | (n+18)+2n=90 | | -23=2x+3x+2 | | x/3-3=-2 | | 6(x/6)-6(4)=6(x/6) | | -17x+18=13 | | x-7=1-9 | | -7=5-2n+6n | | a+(a-15)=55 | | -8-n=0 | | 8p+3=3p+13 | | 5n+3=14-5n | | -2x+5-5x=5 | | 68mi/h=mi/sec | | (-14xy^2)/(21y^3)= | | 8x-(3x-11)=36 | | 4y=2x+9solve | | 3b^2+7b-6= | | 0.4x-8=9-0.6x | | -5=6x-4x+1 | | 72+6y=-6y |

Equations solver categories